Concurrent training enhances athletes' strength, muscle endurance, and other measures - Davis, W. J.; Wood, D. T.; Andrews, R. G.; Elkind, L. M.; Davis, W. B. (The Journal of Strength and Conditioning Research, 2008)
We evaluated the effects of concurrent strength and aerobic endurance training on muscle strength and endurance, body composition, and flexibility in female college athletes and compared two concurrent exercise (CE) protocols. Twenty-eight women (mean age, 19.6 years) were divided into two matched groups and evaluated before and after a vigorous, 11-week, 3-days per week CE training program. One group did serial CE consisting of a warm-up, resistance exercises at low heart rate (HR), aerobics, and a range of motion cool down. The other group did integrated CE consisting of aerobics, the same resistance exercises at high HR achieved by cardioacceleration before each set, and the same range of motion cool down. The two protocols were balanced, differing only in the timing and sequence of exercises. Serial CE produced discernible (p < 0.05) increases in lower- (17.2%) and upper- (19.0%) body muscle strength and fat-free mass (FFM) (1.8%) and trends toward greater lower-body muscle endurance (18.2%) and reduced upper-body flexibility (-160.4%). Integrated CE produced discernible increases in lower- (23.3%) and upper- (17.8%) body muscle strength, lower-body muscle endurance (27.8%), FFM (3.3%), and lower-body flexibility (8.4%) and a decline in fat mass (-4.5%) and percent body fat (-5.7%). Integrated CE produced discernibly larger gains than serial CE for six of nine training adaptations. Effect sizes were generally moderate (44.4% of discernible differences) to large (33.3%). We conclude that serial CE produces adaptations greater than those reported in the literature for single-mode (strength) training in athletes, whereas integrated CE produces discernibly greater gains than serial CE. The results suggest synergy rather than interference between concurrent strength and aerobic endurance training, support prescription of CE under defined conditions, establish the importance of exercise timing and sequence for CE program outcomes, and document a highly effective athletic training protocol.